Intrinsic Gene Expression Correlates of the Biophysically Modeled Diffusion Magnetic Resonance Imaging Signal - Ajay P. Singh; Michael Fromandi; Daniel Pimentel-Alarcón; Donna M. Werling; Audrey P. Gasch; John-Paul J. Yu (Biological Psychiatry Global Open Science)
Magnetic resonance imaging (MRI) is a powerful tool to identify the structural and functional correlates of neurological illness but provides limited insight into molecular neurobiology. Using rat genetic models of autism spectrum disorder, we show that image texture–processed neurite orientation dispersion and density imaging (NODDI) diffusion MRI possesses an intrinsic relationship with gene expression that corresponds to the biophysically modeled cellular compartments of the NODDI diffusion signal. Specifically, we demonstrate that neurite density index and orientation dispersion index signals are correlated with intracellular and extracellular gene expression, respectively. Moreover, we further demonstrate that these imaging signals correlate with genes specifically relevant to the etiopathogenesis of autism spectrum disorder. In sum, our data suggest fundamental relationships between gene expression and diffusion MRI, implicating the potential of diffusion MRI to probe causal neurobiological mechanisms in neuroimaging phenotypes in autism spectrum disorder.